Artificial Intelligence in Sustainable Tourism- Advance Efficiency and Resource Management in Hospitality - Rasel, Mohammad Abul Basher; Islam, MD Rahimul; Siddiqi, Md Tanvir Hasan (International Journal of Computing Sciences Research; Vol 9 (2025): Volume 9, 2025)
Purpose – This study explores how artificial intelligence (AI) can promote sustainable tourism, specifically in the areas of resource management and efficiency in the hospitality industry, while addressing related socioeconomic and environmental issues. Method – This study uses a mixed-methods approach to examine how AI applications, such as predictive analytics, energy management systems, smart technologies, and AI-based tools, can optimize resources, improve energy efficiency, and increase visitor engagement in the hospitality industry. It does this by methodically reviewing industry reports, scholarly sources, and social media content. Results – According to the findings, AI-driven solutions greatly promote sustainable tourism by reducing waste, increasing operational and energy efficiency, and encouraging responsible consumption and climate action. This is particularly in line with Sustainable Development Goals (SDGs) like Clean Energy (SDG 7), Responsible Consumption (SDG 12), and Climate Action (SDG 13). However, obstacles like algorithmic bias, high implementation costs, and data privacy issues prevent AI technologies from being widely adopted in the industry. Conclusion – AI is essential to achieving sustainability goals and improving operational efficiency in the hospitality sector. To fully realize AI's potential for environmental and socioeconomic advancement in tourism, broader adoption, uniform sustainability metrics, and ethical frameworks are necessary. Recommendation – The goals of future research should be to create standardized frameworks for sustainability assessments, create scalable and reasonably priced AI solutions for SMEs, and investigate the ethical and industry-specific ramifications of AI use in sustainable tourism. Research Implications – By highlighting areas for further research, especially in the scaling and equitable implementation of AI technologies within the industry, this article enhances the body of knowledge on AI's contributions to sustainable tourism and hospitality.